Allelopathy of Piptadenia moniliformis and Capparis hastata on the vigor of Mimosa hostilis seeds (Research, Society and Development, 2020)
Reforestation has been encouraged around the world for providing an improvement in the terrestrial ecosystem, so to be successful it is necessary to use plant species that are compatible with each other, with the absence of inhibitory properties that affect and harm the establishment and thereby restrict efficiency reforestation. In the present study, the objective was to verify possible allelopathic effects exerted by aqueous extracts of fresh leaves of Capparis hastata and Piptadenia moniliformis on the physiological characteristics of seeds of Mimosa hostilis. A completely randomized design with five treatments and five replications was used for each species. The scientific methodology used in this experiment was laboratory research using the quantitative method. The crude extract (100%) of each species was diluted, in concentrations 25; 50 and 75%; distilled water (0%) was used for the control. The percentage of emergence, speed index, mean time of emergence, length and dry mass of the aerial part and root system were determined. The results demonstrated that the aqueous extracts of the leaves of C. hastata and P. moniliformis have inhibitory properties in the germination and initial development of M. hostilis, being necessary to proceed with caution regarding the spacing between species when adopting a reforestation program.